TENDENCY IN DEVELOPMENT OF THE MIX PREPARATION SYSTEMS - V. F. Odinochko; D. L. Kostylev (Литьë и металлургия, 2007)
The system of automation of the mix preparation process using control of the sands specific humidity by means of microwave methods is developed.